Persepsi dan Minat Mahasiswa terhadap Studi Manajemen ZISWAF di Perguruan Tinggi Islam - Bayinah, Ai Nur; Amirudin, Amirudin; Ummi Kulsum, Robi’ah (Islamic Management and Empowerment Journal, 2026)
This study aims to examine students’ perceptions and interests in choosing the Zakat, Infaq, Sadaqah, and Waqf (ZISWAF) Management concentration at the Da’wah Management Study Program, Faculty of Da’wah and Communication Sciences, UIN Syarif Hidayatullah Jakarta. A quantitative survey was conducted involving students from the 2021–2023 cohorts using a Likert-scale questionnaire. The data were analyzed using descriptive statistics and simple linear regression. The results indicate that most students have positive perceptions and interests toward ZISWAF Management; however, the actual number of students selecting this concentration remains relatively low. Students’ perceptions have a positive and significant effect on their interest in choosing the concentration (R² = 0.803; p < 0.001). The main factors influencing students’ interest include understanding and motivation, career prospects, teaching methods, learning materials, the learning environment, and academic management and policies. The study recommends strengthening practice-based curricula, promoting digital learning innovation, expanding collaboration with ZISWAF institutions, and enhancing career information to increase the attractiveness of the ZISWAF Management concentration.